Uçak Yapılarında Yorulma Ve Çatlak İlerlemesi - Atagündüz, Sabriye Sera (Fen Bilimleri Enstitüsü, 2015)
Havacılık endüstrisi, uçak yapılarında metallerin kullanımının hızla artmasıyla birlikte yorulma ve çatlak ilerlemesi sorunlarıyla her geçen gün daha fazla karşı karşıya kalmaya başlamıştır. Bu çalışmanın amacı, uçak yapılarında yorulma ve çatlak ilerleyişi davranışını, analitik bir yöntemle sunmaktır. Bu çalışmada üç farklı geometriye köşe çatlağı modellemesi, örnek bir uçak gövdesi paneline de boylamasına çatlak modellemesi uygulanmıştır. Dairesel bir delik etrafında köşe çatlağı oluşması, uçak yapılarının ömrü üzerindeki etkisinden dolayı kırılma mekaniği otoritelerinin oldukça fazla dikkatini çeken bir konu olmuştur. Bu çalışmadaki esas amaç, boylamasına bir çatlağın uçak gövde panelindeki ilerleyişinin, gerçek veriler ve yapılan analitik çalışma arasındaki yakınsaklığının gözlemlenmesidir. Çatlak ilerleyişi analitik olarak hesaplanmış, gerçek çatlak ilerleyiş verileri ile karşılaştırılmıştır. Analiz sonuçlarında, önerilen yöntemlerle geliştirilen analitik formülasyonun mühendislik açısından yeter yakınsaklığı sağladığı görülmüştür.

The aviation industry has been plagued with fatigue failures ever since the vastly increased use of metals during the industrial revolution. The purpose of this study is to present a simplified semi-analytical methodology to predict the behaviour of fatigue and cracks in aircraft structures. In this study the models analysized are corner cracks applied to three different geometries and a longutidinal crack above a broken frame in a curved stiffened panel. The problem of corner cracks at a circular hole configuration has received considerable attension from the fracture mechanics community because of its effect on the life of aircraft structures. The main goal is to correlate the propagation behaviour of a longitudinal crack for another stiffened curved panel as determined with the numerical curved model. The methodology is based mainly on the application of “bulging” coefficients to stress intensity factors taken from a numerical model of a stiffened cracked panel in order to get the crack driving force of the curved panel. A crack above a broken frame is taken into account in modelling the longitudinal crack on the fuselage panel. The panel has test data of the non-uniform stress distribution. The basic formulation used is the Forman Equation. The bulging phenomenon is included in the stress intensity factor calculations by using the formulation of Swift. The Crack propagation is calculated and compared with the actual test results. Analysis of the results shows a highly satisfactory correlation between prediction by calculation and experimental data.
Fatigue Failure And Crack Propagation In Aircraft Structures
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2004
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2004
Keywords: Yorulma ve Çatlak İlerleyişi; Analitik Yöntem; Gövde Paneli; Fatigue; Crack Propagation; Analytical Method; Fuselage Panel